1997
DOI: 10.1093/ajcn/66.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tea flavonoid supplementation on the susceptibility of low-density lipoprotein to oxidative modification

Abstract: Dietary flavonoid intake has been reported to be inversely associated with the incidence of coronary artery disease. To clarify the possible role of tea flavonoids in the prevention of atherosclerosis, we investigated the effects of tea flavonoids on the susceptibility of low-density lipoprotein (LDL) to oxidative modification. In an in vitro study, catechins or theaflavins (25-400 mumol/L) were added to plasma and incubated for 3 h at 37 degrees C. Then, the LDL fraction was separated by ultracentrifugation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(130 citation statements)
references
References 27 publications
3
123
1
3
Order By: Relevance
“…Many experiments have shown that catechins with a galloyl moiety, such as ECg and EGCg, have more effective biological activities than their homologues lacking the galloyl group, including growth inhibition of a human lung cancer cell line: ECgϾEGCgϾEGCϾEC (23); antibacterial activity against Helicobactor pylori, EGCgϾECgϾEGCϾEC (5); inactivation effects on human type-A influenza virus, ECgϾEGCgϾ ϾEGC (6); and inhibitory effects on the oxidative modification of LDL, EGCgϾECgϾEGCϾEC or EGCgϾECgϾ ϾECϾEGC (24,25). These results indicate that the activities of ECg and EGCg were always higher than those of EC and EGC.…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments have shown that catechins with a galloyl moiety, such as ECg and EGCg, have more effective biological activities than their homologues lacking the galloyl group, including growth inhibition of a human lung cancer cell line: ECgϾEGCgϾEGCϾEC (23); antibacterial activity against Helicobactor pylori, EGCgϾECgϾEGCϾEC (5); inactivation effects on human type-A influenza virus, ECgϾEGCgϾ ϾEGC (6); and inhibitory effects on the oxidative modification of LDL, EGCgϾECgϾEGCϾEC or EGCgϾECgϾ ϾECϾEGC (24,25). These results indicate that the activities of ECg and EGCg were always higher than those of EC and EGC.…”
Section: Discussionmentioning
confidence: 99%
“…The content of resveratrol in grape determines the natural resistance to the fungus Botrytis cinerea (gray mold) (19). After (22,23), the isoflavonoids kievitone and phaseollin in beans (24)(25)(26), anid the catechins epicatechin and epigallocatechin in green tea (27). Catechins (25).…”
Section: Distribution and Ecologic Functions Biochemistry Ofselected mentioning
confidence: 99%
“…They occur in relatively high concentrations in fruits, vegetables, nuts and grains, and in various herbs and spices. Examples are the flavanones naringenin and sakuranetin in rice (Rakwal et al, 1996;Kodama, 1996), the isoflavonoids kievitone and phaseollin in beans (Goossens, 1987;Stossel & Magnolato, 1983;Liu et al, 1995) and the catechins epicatechin and epigallocatechin in green tea (Ishikawa et al, 1997). Catechins and flavan-3,4-diols can polymerize to polyflavonoids called condensed tannins.…”
Section: Introductionmentioning
confidence: 99%